Charlotte Mew and her friends / Penelope Fitzgerald. - Fitzgerald, Penelope (Flamingo, 2002)
Charlotte Mew was a poet with a formidable reputation. Outwardly, she also was a dutiful daughter living at home with an ogre of a mother. However, proprieties had to be observed and no one could know that they had no money, that two siblings were insane and that Charlotte was a lesbian.